Sexually-transmitted monkeypox: report of two cases - Lopes, Paula Sian; Haddad, Gabriela Roncada [UNESP]; Miot, Helio Amante [UNESP] (Elsevier B.V., 2022)
Monkeypox is an emerging infection that has spread to all continents since May 2022. It is caused by the zoonotic monkeypox virus, consisting of double-stranded DNA, belonging to the Orthopoxvirus genus of the Poxviridae family, which has high transmissibility, especially by contact with the skin, favoring its sexual transmission. This case report describes a same-sex male couple, both aged 28 years old, without comorbidities. In the index case, perioral and penile lesions started ten days before the consultation, with rapid progression and a high fever that started eight days after the appearance of the lesions. In the second case, the periorat lesions started three days after the partner; however, he remained afebrile. Both were isolated, treated with symptomatic measures, and, after ulceration, the lesions completely regressed in 14 days. Dermatologists should be aware of manifestations of monkeypox, which may include vesiculopustular lesions in areas of sexual contact, as well as oligosymptomatic cases or cases with few skin lesions. (C) 2022 Sociedade Brasileira de Dermatologia. Published by Elsevier Espana, S.L.U.
Keywords: Monkeypox; Sexually transmitted diseases; Sexually transmitted diseases, viral